Conditional Cash Transfers : Reducing Present and Future Poverty - Fiszbein, Ariel; Schady, Norbert; Ferreira, Francisco H.G.; Grosh, Margaret; Keleher, Niall; Olinto, Pedro; Skoufias, Emmanuel (Washington, DC: World Bank, 2012)
The report shows that there is good evidence that conditional cash transfers (CCTs) have improved the lives of poor people. Transfers generally have been well targeted to poor households, have raised consumption levels, and have reduced poverty, by a substantial amount in some countries. Offsetting adjustments that could have blunted the impact of transfers, such as reductions in the labor market participation of beneficiaries, have been relatively modest. Moreover, CCT programs often have provided an entry point to reforming badly targeted subsidies and upgrading the quality of safety nets. The report thus argues that CCTs have been an effective way to redistribute income to the poor, while recognizing that even the best-designed and best-managed program cannot fulfill all of the needs of a comprehensive social protection system. CCTs therefore need to be complemented with other interventions, such as workfare or employment programs and social pensions. The report also considers the rationale for conditioning the transfers on the use of specific health and education services by program beneficiaries. Conditions can be justified if households are under investing in the human capital of their children, for example, if they hold incorrect beliefs about the returns to these investments; if there is "incomplete altruism" between parents and their children; or if there are large externalities to investments in health and education. Political economy considerations also may favor conditional over unconditional transfers: taxpayers may be more likely to support transfers to the poor if they are linked to efforts to overcome poverty in the long term, particularly when the efforts involve actions to improve the welfare of children.